Associations between psychological wellbeing, depression, general anxiety, perceived social support, tooth brushing frequency and oral ulcers among adults resident in Nigeria during the first wave of the COVID-19 pandemic - Morenike Oluwatoyin Folayan; Olanrewaju Ibikunle Ibigbami; Ibidunni Olapeju Oloniniyi; Olakunle Oginni; Olutayo Aloba (BMC, 2021)
Abstract Introduction The aims of this study were to determine the associations between psychological wellbeing, and the frequency of tooth brushing and presence of oral ulcers during the COVID-19 pandemic; and to identify the mediating roles of psychological distress (general anxiety and depression) and perceived social support in the paths of observed associations. Methods This cross-sectional study recruited 996 adults in Nigeria between June and August 2020. Data collected through an online survey included outcome variables (decreased frequency of tooth brushing and presence of oral ulcers), explanatory variable (psychological wellbeing), mediators (general anxiety symptoms, depression symptoms and perceived social support) and confounders (age, sex at birth, educational and employment status). Multivariate logistic regression was used to determine the risk indicators for the outcome variables. A path analysis was conducted to identify the indirect effect of mediators on the association between the outcome and explanatory variables. Results Of the 966 respondents, 96 (9.9%) reported decreased tooth-brushing frequency and 129 (13.4%) had oral ulcers during the pandemic. The odds of decreased tooth-brushing during the pandemic decreased as the psychological wellbeing increased (AOR: 0.87; 95% CI: 0.83-0.91; p < 0.001) and as generalized anxiety symptoms increased (AOR: 0.92; 95% CI: 0.86-0.98; p = 0.009). The odds of having an oral ulcer was higher as the generalized anxiety symptoms increased (AOR: 1.15; 95% CI: 01.08-1.21; p < 0.001). Only generalized anxiety (indirect effect: 0.02; 95% CI: 0.01-0.04; P = 0.014) significantly mediated the relationship between wellbeing and tooth-brushing accounting for approximately 12% of the total effect of wellbeing on decreased toothbrushing. Generalized anxiety (indirect effect 0.05; 95% CI: − 0.07-0.03; P < 0.001) also significantly mediated the relationship between wellbeing and presence of oral ulcer accounting for 70% of the total effect of wellbeing on presence of oral ulcer. Depressive symptoms and perceived social support did not significantly mediate the associations between psychological wellbeing, decreased frequency of tooth brushing and the presence of oral ulcers. Conclusion Patients who come into the dental clinic with poor oral hygiene or oral ulcers during the COVID-19 pandemic may benefit from screening for generalized anxiety and psychological wellbeing to identify those who will benefit from interventions for mental health challenges.